Review of mental health transport needs of people subject to the Mental Health Act (MHA). (1st April 2018) - Pugh, David; Gluck, Karl; Buckley, Linda
An electronic survey was undertaken in the period March–June 2016 to assess the experience of people who had been transported under the Mental Health Act 1983 (MHA). The location of the survey was the South West of England. The questions asked related to the individual's experience of using transport, the time taken to be transported, what was good about the journey, what was unsatisfactory and what could be done to improve the experience. There were 16 responses in total. The findings have been summarised into five main themes: physical comfort, transport type, transport time, professional approach and monitoring. People who had been transported reported that the current method of transport (either via the police or NHS ambulance services) had led to them feeling stigmatised and that there was often a lack of understanding from these agencies around the specific needs of people with mental health conditions. In general, individuals subject to the MHA faced a long wait for some form of transportation. There was a preference for transport in a car, as opposed to a police vehicle or ambulance.